STUDI LITERATUR REVIEW UJI EFEKTIVITAS TANAMAN BELIMBING WULUH (AVERRHOA BILIMBI L.) SEBAGAI ANTIDIABETES: STUDI LITERATUR REVIEW UJI EFEKTIVITAS TANAMAN BELIMBING WULUH (AVERRHOA BILIMBI L.) SEBAGAI ANTIDIABETES - Amelia Sholu Pratiwi; Melia Eka Rosita (JURNAL FARMASI DAN KESEHATAN INDONESIA, 2022)
Diabetes mellitus is a disease caused by a chronic disorder that occurs when the pancreas produces enough insulin or the body cannot effectively use the insulin it produces. Belimbing wuluh (Averrohoa bilimbi L.) is an antidiabetic plant. The plant parts that can be used are the fruit and leaves of star fruit. It can be seen that Belimbing wuluh contains carotenoid compounds, anthocyanins, flavonoids, phenolic compounds, saponins, and alkaloids which are thought to be antidiabetic. The literature review study of this journal aims to provide information about giving starfruit plants to reducing blood glucose levels for alternative therapies. This literature review study was made using qualitative methods using a descriptive non-experimental research design, which was compiled using data from national journals and websites published from 2018-2021 through a literature search process related to the effectiveness of star fruit (Averrohoa bilimbi L.) . The results of this study indicate that the starfruit plant, both leaves and fruit, ethanol extract, and water fraction have effectiveness in reducing blood glucose levels. Keywords: Antidiabetic, wuluh starfruit plant extract